Morrison's miracle the 2019 Australian federal election - Gauja, Anika; Sawer, Marian 1946-; Simms, Marian (Australian National University Press, 2020)
This book, the 17th in the federal election series and the ninth sponsored by the Academy of the Social Sciences in Australia, provides a comprehensive account of the 2019 Australian election, which resulted in the surprise victory of the Coalition under Scott Morrison. It brings together 36 contributors who analyse voter behaviour, campaign strategies, regional variations, polling, ideology, media and the new importance of memes and digital campaigning. Morrison’s victory underlined the continuing trend toward the personalisation of politics and the loss of trust in political institutions, both in Australia and across western democracies. Morrison’s Miracle is indispensable for understanding the May 2019 Coalition victory, which surprised many observers and confounded pollsters and political pundits
Keywords: Morrison, Scott / 1968-; Australia / Parliament / Elections / 2019; Elections / Australia / 2019; Political campaigns / Australia / 21st century; Australia / Politics and government / 21st century; Australia / Parliament; Elections; Political campaigns; Politics and government; Australia; 2000-2099; Electronic books; Aufsatzsammlung